Lahirnya Pancasila : Pembentukan Pancasila Sembilan dan Piagam Jakarta - Katriya, cinta (Maliki Interdisciplinary Journal, 2025)
Pancasila is the fundamental ideology of Indonesia, born from a long historical and philosophical process. It functions not only as the foundation of the state but also as a moral and political guide that unites the diversity of Indonesian society. This article explores the background of Pancasila’s formation by tracing its roots in local values, pre-independence socio-political dynamics, and the spirit of compromise among the nation’s founders. The study reveals that Pancasila represents a synthesis of religious, humanistic, and national values formulated through dialogue and deliberation. Therefore, Pancasila remains highly relevant as an ethical and ideological foundation for maintaining national unity and addressing the complex challenges of modern society.